THE TRADITION OF THE PRACTICE OF MONEY LOANS WITH GUARANTEE OF RICE HARVEST IN THE TANGGA BOSI COMMUNITY: ANALYSIS OF MAQASHID SHARIA - Asrul Hamid; Resi Atna Sari Siregar; Filda Elisa Nasution (Ijtihad, 2022)
The concept of borrowing and borrowing (al-qardh) in Islam is an approach to tabarru' to Allah with the aim of getting His pleasure. This is a form of concern for fellow human beings, especially for people who are struggling with life's difficulties, so that the loans given are able to ease the burden of life for those who are in trouble. Loans in Islam must be separated from commercial or profit-oriented elements, because it is a pure contract of mutual assistance as a form of devotion to Allah Swt. As for the tradition of the Tangga Bosi community, Siabu District, Mandailing Natal Regency, North Sumatra, that when the rice planting season arrives, the majority of people who are farmers will borrow money from rice mill traders to provide capital for cultivating rice fields and also for daily needs with guaranteed yields. When the rice is harvested, it must be sold to the merchant who provided the loan at a price determined by the merchant. The results of the study concluded that the practice of borrowing and borrowing carried out by the Tangga Bosi community with the concept they agreed upon was not in accordance with Islamic teachings because of the taking of benefits or profits on one side, then guaranteeing the rice yields which could not be guaranteed to be successful or not (gharar). However, if you are in a state of urgency or emergency after all efforts have been made but no solution is found, then this kind of lending practice is allowed because it is feared that without this loan cultivation of rice fields will not work and will bring greater mafsadat so that it interferes with the five main elements of the goal shari'ah is established (maqashid shari'ah).